Application of the Vienna Classificaton for Crohn's Disease to a Single Clinician Database of 877 Patients - Hugh James Freeman (Canadian Journal of Gastroenterology)
An international working party at the World Congress of Gastroenterology held in Vienna, Austria from September 6 to 11, 1998 defined a classification for Crohn's disease based on patient age at diagnosis (eg, less than 40 years of age, 40 years of age or older), disease location (eg, terminal ileum, colon, ileocolon or upper gastrointestinal tract) and behaviour (eg, stricturing, penetrating). Disease location in the upper gastrointestinal tract was defined by disease being present proximal to the terminal ileum, regardless of terminal ileal or colon involvement. A 20-year, single clinician database of 877 patients from a university campus hospital was used, and comprised 492 women (56.1%) and 385 men (43.9%). Of these patients, 740 (84.4%) were diagnosed before age 40 years and 137 (15.6%) were diagnosed by 40 years of age or older. Disease was located in the terminal ileum alone in 222 patients (25.3%), colon alone in 238 patients (27.2%) and ileocolon in 304 patients (34.6%). Another 113 patients (13.1%) had disease in the upper gastrointestinal tract, usually with disease also in the terminal ileum (23 patients), colon (12 patients) or ileocolon (71 patients). Only seven of 877 patients had disease located in the upper gastrointestinal tract alone with no distal disease. Disease behaviour could be classified as nonstricturing and nonpenetrating in 256 patients (29.2%), stricturing in 294 patients (33.6%) and penetrating in 327 patients (37.2%). Of the 877 patients with Crohn's disease, 837 were white, 38 were Asian and two were black. In this tertiary care setting of a single clinician practice in a Canadian teaching hospital at the University of British Columbia, Crohn's disease predominantly affects women, and young adults with a high rate of stricturing and penetrating complications.